1985
DOI: 10.1029/jb090ib03p02495
|View full text |Cite
|
Sign up to set email alerts
|

The near‐Earth magnetic field at 1980 determined from Magsat data

Abstract: Data from the Magsat spacecraft for November 1979 through April 1980 and from 91 magnetic observatories for 1978 through 1982 are used to derive a spherical harmonic model of the earth's main magnetic field and its secular variation at epoch 1980.0. The model is called GSFC(12/83). Constant coefficients are determined through degree and order 13 and secular variation coefficients through degree and order 10. The first‐degree external terms and corresponding induced internal terms are given as a function of Dst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(107 citation statements)
references
References 20 publications
4
102
1
Order By: Relevance
“…The mean Dst for the (filtered) POGS data is -10.0 nT, with a range of -46.0 nT to +28.3 nT. Thus (g1°,g11,s11) = (+20.1,-4.4,x.3) nT here can be described as being in reasonable agreement with Langel and Estes (1985b), although not strictly consistent with their observed Dst dependence of external coefficients. However, there may be longer term, periodic, variations in average external fields.…”
Section: External Field Coefficients and Main-field Modelssupporting
confidence: 76%
See 1 more Smart Citation
“…The mean Dst for the (filtered) POGS data is -10.0 nT, with a range of -46.0 nT to +28.3 nT. Thus (g1°,g11,s11) = (+20.1,-4.4,x.3) nT here can be described as being in reasonable agreement with Langel and Estes (1985b), although not strictly consistent with their observed Dst dependence of external coefficients. However, there may be longer term, periodic, variations in average external fields.…”
Section: External Field Coefficients and Main-field Modelssupporting
confidence: 76%
“…If we express the firstthree external field coefficients as a triplet (q 1°,q l 1 sl '),in a conventional notation, e.g., Langel and Estes (1985b), Langel (1987), we find that for the baseline model with added external (inclined) dipole, (q1°,g11,s11) = (+21.7,-6.8,-6.7) nT. In comparison the "best" POGS-based model, derived in Subsection 3.5 from a data set with a larger proportion of POGS data, results in (g1°,g11,s11) = (+20.1,-4.4,-4.3) nT.…”
Section: External Field Coefficients and Main-field Modelsmentioning
confidence: 99%
“…However, none of these indices assesses the absolute baseline of the quite-time magnetospheric field. Based on Magsat vector data the quiet-time magnetospheric field level was first estimated as 20 nT by Langel & Estes (1985a) and Langel & Estes (1985b). This first approximation was then specified using 9 yr of CHAMP data that revealed a stable quiet-time field of 13 nT with an additional variable part of up to 15 nT depending on the solar cycle phase .…”
Section: Introductionmentioning
confidence: 99%
“…A small, but significant difference in the amplitude of ring current magnetic signatures between LEO satellites and ground has been noticed in earlier years (e.g., Langel and Estes 1985b;Olsen 2002;Maus and Lühr 2005). Recently, Le et al (2011) compared C/NOFS satellite observations with the Dst-index for selected geomagnetic storms and found that the satellite observations have only about 80% amplitude of the signatures at ground.…”
Section: This Issue)mentioning
confidence: 99%